2015
DOI: 10.2460/javma.246.1.118
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of pharmacokinetics and milk elimination of flunixin in healthy cows and cows with mastitis

Abstract: Pharmacokinetics and elimination of flunixin and 5-hydroxy flunixin in milk differed between mastitic and healthy cows, resulting in violative residues. This may partially explain the high number of flunixin residues reported in beef and dairy cattle. This study also raised questions as to whether healthy animals should be used when determining withdrawal times for meat and milk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
75
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(86 citation statements)
references
References 38 publications
9
75
2
Order By: Relevance
“…Compared with the FLU PK parameters reported by Kissell et al. (), we found similar values for MRT but higher values for V area and CL. We also report substantially lower values for AUC.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Compared with the FLU PK parameters reported by Kissell et al. (), we found similar values for MRT but higher values for V area and CL. We also report substantially lower values for AUC.…”
Section: Discussionsupporting
confidence: 78%
“…We detected FLU in plasma samples up to 30 hr post‐treatment, 18 hr longer than reported by Kissell et al. (); however, we implemented lower LOD and LOQ levels. Mean FLU protein binding was determined to be 98.6% in both treatment groups, which is slightly lower than values reported by Anderson et al.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Numerous studies have shown that disease alters the pharmacokinetics of various drugs2101531. The degree of pharmacokinetic changes depends on the severity of the disease.…”
Section: Methodsmentioning
confidence: 99%
“…Subsequent studies are then conducted employing this fixed ratio in larger number of healthy animals to determine a withdrawal time after cessation of drug administration that will deplete target tissues to below the TOL or MRL for the marker residue. Due to these flaws, violative drug residues in the edible tissues of food-producing animals may occur when drugs are used in an extralabel manner or when disease is present even though the animals are slaughtered according to regulatory labeled withdrawal times23. Commonly reported drug violations include ceftiofur, enrofloxacin, flunixin, and sulfamethazine4.…”
mentioning
confidence: 99%